PENGEMASAN PAKET WISATA DENGAN MEMANFAATKAN POTENSI DESTINASI WISATA ALTERNATIF DI KAWASAN PANTAI PARANGTRITIS - Fiyan, Miftah Arif; Rachmadi, Hari (JURNAL MEDIA WISATA: Wahana Informasi Pariwisata, 2018)
Yogyakarta which has a unique culture and nature and also relics of historical and religious relics can be a point of interest for domestic and foreign tourists. With diversity is quite a lot of power. This research is why Alternative Tour Packages will be an attraction if in a pack in such a way that becomes a diverse and interesting tour packages. With qualitative descriptive research methods found in addition to the main destinations Parangtritis Beach which was first famous. With the packaging method of alternative tour packages and promotions will make the new destinations become the main and complementary destination support power for a visit in Yogyakarta. Can be condluded that Parangtritis which became the main destination for tourists domestic is a region that has the potential to be developed, this area there is destination 1.Nature 2.Religi 3.History 4.Culture but not packaged into a package of alternative tourism. Packaging Alternative Tour Packages in addition to increasing the number of tourists visits also the level of customer satisfaction is increasing because it does not accumulate on one Destination that is Parangtris Beach can be distributed to this destination equally. The results of this research area is the Parangtritis Beach could be developed into an alternative tour package based on the study of researcher. Be a tour package: 1. Nature, include: Parangwedang bathing place, Depok Beach, Parangendog Beach, Gumuk Pasir and Museum Gumuk Pasir, 2. Religion : Makam Syeh Bela Belu and Makam Syeh Maulana Maghribi, 3. History : Gua Jepang, 4. Culture : Cepuri Watu Gilang. . Keywords : Tour package , nature, religi, history, culture, history